The interaction of vision and audition in two-dimensional space - Godfroy-Cooper, Martine; Sandor, Patrick M.; Miller, Joel D.; Welch, Robert B. (Frontiers in Neuroscience, 2015)
Using a mouse-driven visual pointer, 10 participants made repeated open-loop egocentric localizations of memorized visual, auditory, and combined visual-auditory targets projected randomly across the two-dimensional frontal field (2D). The results are reported in terms of variable error, constant error and local distortion. The results confirmed that auditory and visual maps of the egocentric space differ in their precision (variable error) and accuracy (constant error), both from one another and as a function of eccentricity and direction within a given modality. These differences were used, in turn, to make predictions about the precision and accuracy within which spatially and temporally congruent bimodal visual-auditory targets are localized. Overall, the improvement in precision for bimodal relative to the best unimodal target revealed the presence of optimal integration well-predicted by the Maximum Likelihood Estimation (MLE) model. Conversely, the hypothesis that accuracy in localizing the bimodal visual-auditory targets would represent a compromise between auditory and visual performance in favor of the most precise modality was rejected. Instead, the bimodal accuracy was found to be equivalent to or to exceed that of the best unimodal condition. Finally, we described how the different types of errors could be used to identify properties of the internal representations and coordinate transformations within the central nervous system (CNS). The results provide some insight into the structure of the underlying sensorimotor processes employed by the brain and confirm the usefulness of capitalizing on naturally occurring differences between vision and audition to better understand their interaction and their contribution to multimodal perception.